If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(5x + -5) = -70 Reorder the terms: -7(-5 + 5x) = -70 (-5 * -7 + 5x * -7) = -70 (35 + -35x) = -70 Solving 35 + -35x = -70 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + -35x = -70 + -35 Combine like terms: 35 + -35 = 0 0 + -35x = -70 + -35 -35x = -70 + -35 Combine like terms: -70 + -35 = -105 -35x = -105 Divide each side by '-35'. x = 3 Simplifying x = 3
| (4xy-3y^2)dx+(2xy-2x^2)dy=0 | | 22/3×=10 | | -10.2-x=12.8 | | 3x+5x-2x=180 | | R/5=.8 | | -50+6=12u+62 | | B+25+5=2 | | 2/3k=28×4/9 | | 72=4r | | 2.75x=10 | | -50+6=120+62 | | 6x-20+3x+10=180 | | -4(-12-12v)=8(7v-10) | | 15x+7=127 | | 1/4y-11=47 | | 7+12lnx=5 | | 2m+128=180 | | -7(3x+1)=119 | | d+11=20 | | 9=33+b | | 21x=45 | | 3/5z=33 | | -y+4=8y-6 | | 9d-9+9d-9=180 | | 5/2*5/12 | | 5+.1n+.2n-2+.4n=21 | | 3x+5x-2=180 | | Z/5=24 | | 9d-9=180 | | 5-2+3+3= | | x^2+16+55=0 | | 37+p=21 |